Radionuclide transport at the geosphere-biosphere interface : a combined measurements and modelling study - Al Mahaini, Talal (2012)
The aim of the present work was to improve the predictive capabilities of current modelling methods used to assess the long-term biosphere impacts of underground repositories for radioactive wastes. A number of issues related to parameter and conceptual uncertainties associated with compartmental biosphere models that simulate transport and accumulation of radionuclides in soils were addressed. The structure of compartmental models used for radiological risk assessments has not evolved noticeably over the past few decades and most of these models rely on simple assumptions. For example, compartmental models used to predict activity concentrations of radionuclides released into soils over very long timescales (typical of the lifetime of underground disposal repositories) assume arbitrary model specifications such as soil layer thickness (the vertical discretisation of the soil column) and length of the time step. Moreover, the majority of the available models assume invariant sorption characteristics of radionuclides with soil depth and hence employ constant solid-liquid distribution coefficient (Kd) values regardless of soil characteristics known to affect radionuclide sorption (e.g. pH, redox potential, moisture content and organic matter). The empirical Kd has a profound effect on long-term predictions of radionuclide behaviour in soil since it determines the degree of radionuclide retardation due to interaction with the soil. It is associated with considerable uncertainty due to differences in experimental conditions and methods used for its measurement and the variation in soil characteristics. In this study, three soil types (arable, grassland and woodland) were incubated under anaerobic conditions and the behaviour of naturally occurring selenium, iodine, rhenium and uranium, expressed as Kd, was investigated. The results indicate that variation in soil characteristics (e.g. moisture content, pH, mineral and organic carbon content) is a significant source of K, variability. Soils relatively higher in organic matter content (e.g. top soils) have higher sorptive capacities for trace elements than mineral subsoils and hence higher Kds. Dynamic, complex behaviour of K, under flooded, anaerobic soil condtions was measured over a 3 week period in soil microcosms. This dynamic behaviour was driven by the shift in soil redox potential which was associated with solubilisation of soil organic and mineral (Fe oxide) phases. Overall, the maximum observed variation in K, over the entire incubation period did not exceed 2 orders of magnitude. Biosphere models were constructed which combined a physically-based water flow model and the compartmental approach and used to simulate the long-term vertical distribution of radionuclides in the soil as well as radionuclide dynamics under different environmental conditions. Investigating radionuclide dynamics on a short timescale could only be achieved using models with a daily time step since short-term variation was obscured by a longer (annual) time step. Simulation results give insights into some of the limitations of available biosphere modelling methods for radiological risk assessment that are often overlooked. For example, soil radionuclide activity concentrations calculated using compartmental models are sensitive to the vertical discretisation (i.e. thickness of soil layers into which the soil column is divided) and time step of the model, hence the structure of the model should not be set arbitrarily. The discretisation procedure proposed in the present study may provide a useful framework to select the appropriate structure of biosphere assessment models. With respect to the effect of uncertainty in K, on model calculations, the results show that equilibrium timescales and radionuclide activity concentrations in the soil at equilibrium increase as the K, increases. For example, the time to reach steady state radionuclide activity concentrations in the vegetated topsoil increased 14-fold and 7-fold, respectively, when K, was increased 28-fold, which is a small variation compared to the uncertainty of Kd commonly reported in the literature (e.g. a few orders of magnitude). The Kd also affects short and long-term radionuclide dynamics in soils; the activity concentration of a radionuclide with low Kd (weakly sorbing) is more responsive to seasonal fluctuations in climatic and hydrological conditions than a radionuclide with a large Kd (strongly sorbing). Radionuclide uptake by plant roots, especially those which access highly contaminated soil layers adjacent to the contaminated aquifer, could be an important mechanism that provides a direct pathway between shallow, contaminated aquifers and the soil surface where elavated contamination poses greater risks.